A single centre experience in challenging diagnosis and management of osseous and extraosseous Ewing sarcoma: a case series - Michael, Jeniz Saltin Siluvai; Velappan, Arumugam (International Journal of Advances in Medicine, 2025)
Ewing sarcoma (ES) predominantly affects adolescents and young adults, commonly involving the pelvis, femur, and chest wall. This case series analysed the clinicopathological features and treatment profiles of 12 pediatric and adolescent ES patients treated at Tirunelveli Medical College Hospital, Tamil Nadu, from 2019 to 2023. The peak incidence occurred in the 6–15-year age group, with a female predominance. Osseous ES was the most common subtype, with most patients presenting with localised disease or lung metastases. Treatment included chemotherapy, surgery, and radiotherapy, delivered through a multidisciplinary approach. Survival outcomes varied based on disease extent and response to treatment. Advances in radiotherapy and surgical management of oligometastatic disease, along with multiple chemotherapy cycles, may enhance prognosis. The study highlights the importance of early detection, increased awareness, and structured follow-up protocols in improving outcomes. Tailored, comprehensive management strategies are crucial for addressing the clinical challenges of ES in resource-limited settings.